Monitoraggio innovativo per la gestione dell'inquinamento ambientale provocato da rilasci abusivi di rifiuti l'esperienza del progetto DroMEP - Massarelli, Carmine; Uricchio, Vito Felice; Muolo, Maria Rita; Dongiovanni, Nicola (GEOmedia, 2016)
DroMEP project (Drones for Monitoring and Environmental Protection) provides the definition of a smart methodology testing prototype technologies and operational protocols necessary for identifying and monitoring, both in terms of quality and quantity, the illegal dumping and uncontrolled abandonment of waste, highlighting the presence of hazardous waste, especially friable asbestos. This objective was pursued through the development, integration and deployment of innovative technologies for data acquisition: surveys with UAV equipped with multispectral sensors, infrared and thermal camera, surveys with equipped Videocar, aerial photogrammetric, hyperspectral and thermal sensors, and spectroradiometric acquisitions, acquisitions in the field by the citizens via smartphone app, were carried out. The project also included the creation of a computerized and interoperable platform for managing and sharing integrated different spatial data. The experience has allowed, therefore, the development of a methodology of systematic monitoring and repeatable useful for assessing the environmental quality of territories and the possible presence of risks for citizens. The information acquired, after processing, they are an excellent tool for administrators and decision makers for the evaluation of environmental actions to be implemented for a sustainable programming.